2001
DOI: 10.1111/j.1469-8749.2001.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological disorders related to interictal epileptic discharges during sleep in benign epilepsy of childhood with centrotemporal or Rolandic spikes

Abstract: Nine children (five males, four females; age range 6 years 1 month to 11 years 1 month) affected by benign epilepsy of childhood with centrotemporal or Rolandic spikes (BECRS) with EEG evidence of marked activation of interictal epileptic discharges (IEDs) during sleep, and nine unaffected control children matched for age, sex, and socioeconomic status, were enrolled in a prospective study. At the time of detection of IED activation during sleep, patients showed a mean Full-Scale IQ score within the normal ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 41 publications
5
115
0
1
Order By: Relevance
“…In contrast, several studies have shown that neuropsychological functioning improves with normalization of the EEG. 23 Metz-Lutz et al 4 reported that performances in the neuropsychological assessments were specifically weakened in individuals with active epilepsy with frequent spike-wave discharges on the waking EEG. These findings suggest that the subclinical discharges contribute to the psychosocial problems that are increasingly recognized in rolandic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have shown that neuropsychological functioning improves with normalization of the EEG. 23 Metz-Lutz et al 4 reported that performances in the neuropsychological assessments were specifically weakened in individuals with active epilepsy with frequent spike-wave discharges on the waking EEG. These findings suggest that the subclinical discharges contribute to the psychosocial problems that are increasingly recognized in rolandic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings we assumed that epileptic discharges in sleep may interfere with the development of cognitive linguistic processes, if they manifest at a specific age and are long lasting. [11][12][13] As suggested by Aldenkamp and Arends, 14 the presence of an active epileptic focus may interfere with the normal maturation of cognitive functions but its long-term consequences are yet to be determined. In our patients, drug therapy achieved a good seizure control but it was unsatisfactory in reducing nocturnal paroxysmal electric activity.…”
Section: Discussionmentioning
confidence: 99%
“…The second aim of our study was to search for DCD in children affected by BECTS, a very common idiopathic partial epilepsy in childhood, characterized by excellent prognosis of seizures but not always benign with respect to neuropsychological aspects (Baglietto et al . 2001;Northcott et al .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the definition of 'Benign' , BECTS is frequently associated with learning disabilities (LD), language impairment, attention deficit or clumsiness (Bouquet et al . 1985;Baglietto et al . 2001;Holtmann et al .…”
Section: Introductionmentioning
confidence: 99%